Participation of Housewives in Prevention of Dengue Hemorrhagic Fever in Sub-District Muara Dua, Lhokseumawe, Aceh, Indonesia - Wahyu Ajisah; Irnawati Marsaulina; R. Kintoko Rochadi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Indonesia is a dengue endemic area and it has an epidemic once in 4-5 years. Until now it tends to increase in number of cases as well as its widespread. Researchers investigated that socio-demography, knowledge and attitudes related to dengue disease affecting the participation of housewives in prevention of dengue fever dengue mosquito through questionnaires and interviews. This research was conducted descriptively with cross sectional approach to 72 housewives in sub-district Muara Dua, Lhokseumawe, Aceh, Indonesia using sample purposive sampling process. The relationship between the characteristics of housewives with their involvement in prevention of Dengue Hemorrhagic Fever (DHF) was analyzed using Pearson correlation analysis. More than 75% of respondents live in endemic areas and over 68% of respondents knew that dengue is transmitted through mosquitoes. 50% of respondents knew that 3M (draining the water reservoir, closing the water reservoir and burying the garbage) Plus as DHF prevention but only 37.5% of respondents have applied 3M Plus even though they know that it needs to be continuously done throughout the year especially in the rainy season. The respondents' participation in prevention of DHF disease in moderate category was 50 respondents (69.44%), 9 respondents (12.5%) were categorized as low in participation and only 13 respondents (18.06%) were categorized as very good in participation in the effort to eliminate DHF. There was a highly significant correlation between knowledge and attitude (p <0.01) and there was a significant correlation in education (p <0.05) of housewives with their actions in the prevention of dengue hemorrhagic fever. This reflects the urgent need for advocacy programs in raising awareness of DHF in the community. The nearest inter-sector collaborates with the medical, veterinary, community and local authority sectors to ensure the availability of DHF prevention services besides 3M Plus, also a monitoring officer/home and public health service to undertake health promotion programs of DHF prevention. This is a key element to eliminate deaths from dengue fever which occur every year.